Factors influencing residents’ perceptions, attitudes and behavioral intention toward festivals and special events: a pre-event perspective - Li, Hui; Schein, David D.; Ravi, Siva Prasad; Song, Wei; Gu, Yuanyuan (Journal of Business Economics and Management, 2018)
This article reports the results of research investigating residents’ perceptions, attitudes and behavioral intention (BI) toward sports festivals and special events (FSE) from a pre-event perspective. A structural equation modeling (SEM) was utilized. Two sets of theoretical frameworks have been employed for this study: Social Exchange Theory (SET) and Social Representation Theory (SRT). A quantitative analysis was utilized. Using structural equation modeling (SEM). The authors have identified a strong association between media influence and FSE image evaluation; FSE image evaluation and residents’ perceptions; residents’ perceptions and attitudes; and residents’ attitudes and behavioral intention. However, the study found that social interactions do not have a significant impact on FSE image evaluation. The practical application of this research is that event planners should use media to promote FSE to local residents. This article concludes with the management implications for FSE planners and organizers. Future studies can build on the findings of the paper to generalize this China model for adaption to other countries.